Once again about surrogacy, because human rights violations are increasing as a consequence of the lack of legal framework - Eleonora LAMM (Ars Iuris Salmanticensis, 2016)
This paper seeks to highlight the ever more eloquent, frequent and manifest reality of surrogacy and how the strategies that are being used to remedy or avoid the legal prohibition violate fundamental human rights. It is based on the premisse that the legal prohibition does not prevent the practice, but makes a complex technique even more contentious, violating rights.